2011
DOI: 10.1016/j.ejcts.2011.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Acute renal failure following lung transplantation: risk factors, mortality, and long-term consequences

Abstract: The use of aprotinin and double lung transplantation are associated with ARF following lung transplantation. Age at the time of transplantation and a longer intensive care stay predict decreased survival. ARF after lung transplantation is not predictive of late renal dysfunction or decreased long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 21 publications
5
37
2
Order By: Relevance
“…The prevalence of AKI and RRT in our data were higher than in previous reports (41.2% and 16.2%, respectively), the finding in our study that the need for RRT after lung transplantation increased mortality was similar to previous reports (29,30). Several studies have shown the reasons for the high risk of AKI in recipients of lung transplantation; for example, lung injury could induce inflammatory mediators of the renal epithelium, nephrotoxic agents including calcineurin inhibitors could induce direct injury, and efforts to maintain negative balance might cause kidney injury after transplantation.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The prevalence of AKI and RRT in our data were higher than in previous reports (41.2% and 16.2%, respectively), the finding in our study that the need for RRT after lung transplantation increased mortality was similar to previous reports (29,30). Several studies have shown the reasons for the high risk of AKI in recipients of lung transplantation; for example, lung injury could induce inflammatory mediators of the renal epithelium, nephrotoxic agents including calcineurin inhibitors could induce direct injury, and efforts to maintain negative balance might cause kidney injury after transplantation.…”
Section: Discussioncontrasting
confidence: 57%
“…AKI after lung transplantation developed in 37%, and the incidence of RRT was 5.51% in some previous studies (29,30). The prevalence of AKI and RRT in our data were higher than in previous reports (41.2% and 16.2%, respectively), the finding in our study that the need for RRT after lung transplantation increased mortality was similar to previous reports (29,30).…”
Section: Discussioncontrasting
confidence: 54%
“…In contrast, previous studies reported that age and female sex had a significant effect on better long-term survival. 8,11 Another previous study showed that outcomes in patients who had interstitial lung disease were comparable or better with single than bilateral lung transplant, and short-and long-term survival were not significantly different for the 2 types of procedures. 15 The findings based on United Network for Organ Sharing data showed that bilateral lung transplant had significantly better survival than single lung transplant.…”
Section: Discussionmentioning
confidence: 99%
“…3 The present study did not confirm a significant effect of type of transplant on survival that was previously reported. 8 In 38 patients who had bilateral lung transplant, 19 patients (50%) died soon after surgery because of technical issues, possibly because of more frequent technical complications after bilateral than single lung transplant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation